Optimum Currency Areas : New Analytical and Policy Developments: New Analytical and Policy Developments. (Washington, D.C. : International Monetary Fund, 1997)
Robert Mundell's pioneering theory of optimum currency areas is revisited, with experts from the IMF, the BIS, the European Investment Bank, academia, European think tanks, and the Bank of Israel looking at its current practical applications, especially in the context of the forthcoming European Economic and Monetary Union (EMU). Robert Mundell himself offers an update to help in assessing the implications and consequences of EMU.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet